Flapless versus open flap techniques of implant placement: A 15-month follow-up study - Bhavita Wadhwa; Veena Jain; Ongkila Bhutia; Ashu Seth Bhalla; Gunjan Pruthi (Wolters Kluwer Medknow Publications, 2015)
Aim: To evaluate and compare the effect of flapless and "open flap" techniques of implant placement on crestal bone height (CBH) around implants. Materials and Methods: This prospective study comprised of 32 implants placed in 16 subjects with a bilateral missing mandibular first molar. In each subject, one implant was placed with "flapless" and other using "open flap" technique. Radiographic assessment of CBH was carried out using standardized intraoral periapical radiograph of the site at baseline, 3 months, 9 months and 15 months after implant placement. Statistical Analysis: Data were analyzed using STATA 11.0 statistical software. To determine the changes in CBH from baseline, at 3-, 9-, and 15-month, repeated measures analysis of variance followed by post-hoc Bonferroni was used for each of the two techniques for mesial and distal aspects separately. For both techniques, changes in CBH from baseline to 15 months were compared using an independent t-test with a confidence interval of 95%. Results: For "flapless" technique, there was no statistically significant (P > 0.05) reduction of CBH in initial 9 months but was significant for the 9-15 months period while for "open flap" technique, statistically significant (P < 0.05) reduction was observed up to 15 months. Comparison of both techniques showed significantly lesser reduction with "flapless" than "open flap" technique. The overall average crestal bone loss was 0.046 ± 0.008 mm on mesial aspect, 0.043 ± 0.012 mm on distal aspect with "flapless" technique and 1.48 ± 0.085 mm on mesial aspect, 1.42 ± 0.077 on distal aspect "open flap" technique. Conclusions: Both techniques showed a reduction in CBH with time but the flapless technique showed a lesser reduction. Therefore, the flapless technique can be considered as a better treatment approach for placement of implants, especially where adequate width and height of available bone are present.